2018
DOI: 10.3390/atmos9010027
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Character of Northern Hemisphere Flow Regimes in a Near-Term Climate Change Projection

Abstract: Abstract:The dynamic character of an enstrophy-based diagnostic, previously used in the study of atmospheric blocking, is examined here, in near-term future simulations from the Institut Pierre Simon Laplace Climate Model version 4 (IPSL-CM4) and version 5 (IPSL-CM5) climate models of the Northern Hemisphere flow for moderate climate change scenarios. Previous research has shown that integrated regional enstrophy (IE) increases during blocking onset and decay, which is a reflection of planetary-scale instabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…The classification scheme of reference [6] for NH flows is consistent with the idea that the NH flow has preferred observed states. This idea is not new (see reference [40] for a discussion of the history). The early work of references [52][53][54] (and others) suggested the NH flow vacillated between two quasi-stable states (zonal versus meridional), but later work suggested that the NH flow possesses multiple stable states, including those that represent blocking (e.g., references [55][56][57][58][59]).…”
Section: Discussion: Teleconnection Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…The classification scheme of reference [6] for NH flows is consistent with the idea that the NH flow has preferred observed states. This idea is not new (see reference [40] for a discussion of the history). The early work of references [52][53][54] (and others) suggested the NH flow vacillated between two quasi-stable states (zonal versus meridional), but later work suggested that the NH flow possesses multiple stable states, including those that represent blocking (e.g., references [55][56][57][58][59]).…”
Section: Discussion: Teleconnection Relationshipsmentioning
confidence: 99%
“…The North Atlantic Oscillation (NAO) (e.g., reference [36]) is a north-south pressure oscillation in the North Atlantic whose fundamental dynamics are similar to that of the Pacific North American (PNA) pattern (e.g., references [37][38][39]). The NAO also may be the regional expression of vacillation (e.g., reference [40]) in the NH flow overall. It is well known that the time series of the daily or monthly NAO index values possess interannual (e.g., references [41,42]) or interdecadal (e.g., references [43,44]) modes.…”
mentioning
confidence: 99%
“…This is consistent with the result here, but does not suggest a cause and effect or dynamic relationship between the two. An examination of the wave dynamics would be needed and a recent study [60] suggested that the annual frequency of changes in flow regimes (here ECMs) is not changing significantly or projected to increase in the near future. Additionally, the correspondence between the future occurrence DKV46 NH flow regimes and those examined in studies such as [60] for example has not been examined as yet.…”
Section: Circulation Epochs and Information Entropymentioning
confidence: 99%
“…This study is unique in that this research group is the only one that defines and examines BI across the globe. BI has been shown also to be related to dynamic quantities such as the 500 hPa height gradients [1], enstrophy, and entropy (e.g., Kolmogorov-Saini Entropy [25]). Additionally, this work will compare our results for SH blocking into the 21st century to those of [12] where appropriate.…”
Section: Introductionmentioning
confidence: 99%